The effects of facebook as an learning tool to give peer feedback on students' writing performance a case at an upper secondary school - Lý Thúy Huyên (Trường Đại học Trà Vinh, 2021)
This research is aimed to: Investigate the effects of Facebook as a learning tool to give feedback on students’ writing performance. Identify students’ attitudes towards the use of Facebook as a learning tool in receiving peer feedback on their writing performance